Kajian Wellness Tourism Dari Perspektif Sosial Budaya - Zellius Ragiliawan; Hanif Assabib Rosyid; Rizky Ni'ma Febriani; Budi Santoso; Danang Danang (Jurnal Bengawan Solo Pusat Kajian Penelitian dan Pengembangan Daerah Kota Surakarta, 2023)
The city of Surakarta with an area of 46.72 km2 is known as a city of arts and culture which presents many historical places, various arts and culture, traditions, religion and various craft creations combined with tourism activities. Referring to the information provided by the Culture and Tourism Office of the City of Surakarta, there are several historical tours in the City of Surakarta, namely the Loji Gandrung Building and the Vastenburg Fort. In these places we can trace the history that has occurred in the city of Surakarta. Besides that, Surakarta City also offers other tourist destinations. Other tourist destinations in Surakarta City, namely culinary tourism, batik village tours, cultural tourism, nature tourism, religious tourism, and many others.